Evidence of a Normal-State Pseudogap in Bulk Superconducting Tunneling Junctions of YBa 2 Cu 3 O 7-δ - Guerra, Leandro; Reyes, Mildred; Manuel, Ayn; Sarmago, Roland; Salvador, Arnel (Science Diliman: A Journal of Pure and Applied Sciences, 2007)
Planar contact tunneling experiments have been performed on bulk superconducting tunneling junctions of YBa 2 Cu 3 O 7-δ in the temperature range 77 -295K. A clear depression in the conductance curves measured, attributed to the pseudogap, has been observed in temperatures above Tc (approx. 90K determined from dc resistivity measurements) before disappearing at T*=275K. The width of the pseudogap has been quantitatively measured as Dps, ave = 25.6meV from the differential conductance plots. These results agree with the current understanding of the phenomenology and nature of this pseudogap, namely: (I) the pseudogap value is relatively temperature-independent; (2) the superconducting gap and the pseudogap have the same d-wave nature; and (3) the superconducting gap evolves from the pseudogap.
Keywords: Pseudogap; tunneling; YBa< sub> 2< /sub> Cu< sub> 3< /sub> O< sub> 7-δ< /sub&gt